Efficacy of non-pharmacological interventions for depression in individuals with Parkinson's disease: A systematic review and network meta-analysis - Wang, Yuxin; Sun, Xue; Li, Fei; Li, Qi; Jin, Yi (Frontiers in Aging Neuroscience, 2022)
Background: Depression in Parkinson’s disease (PD) is a popular health concern worldwide. Recently, increasing non-pharmacological interventions have been used in PD to alleviate depressional symptoms. However, it is uncertain to know which intervention is the best and the related evidence is limited. This network meta-analysis was performed to compare and rank non-pharmacological interventions for PD, and analyze their effects on depression, in order to provide evidence for clinicians to choose appropriate non-pharmacological management. Methods: The PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO, China National Knowledge Infrastructure (CNKI) and Wanfang databases were searched from inception to April 7, 2022. Two authors screened all the studies, extracted the data and evaluate methodological quality. The STATA software version 16.0 was used to conduct network meta-analysis. Results: 62 studies on 3,050 participants involving 35 non-pharmacological interventions were included in our network meta-analysis. Although 35 non-pharmacological interventions showed non-significant effects, the SUCRA values indicated that the best non-pharmacological intervention for depression is dance (82.3%), followed by LSVT-BIG therapy (77.4%) and CBT (73.6%). Conclusion: Dance can be considered as an effective therapy for improving depression in PD patients. In the future, more strictly-designed trails are needed to verify the conclusion of this network meta-analysis.